FAKTOR-FAKTOR DETEKSI DINI KANKER LEHER RAHIM PADA WANITA USIA SUBUR DALAM - Suraya, Dewi; Serilaila, Rachmawati, (JURNAL MEDIA KESEHATAN, 2017)
Cervical cancer is a women's health problem in Indonesia, due to high incidence and mortality. The incidence of Cervical Cancer in Indonesia is 16 per 100,000 women. Not performing early detection of cervical cancer on a regular basis and on time is a factor in the spread of cervical cancer. The purpose of this study was to determine the factors that affect WUS in early detection of cervical cancer in Babatan Public Health Center. This research design uses a quantitative approach with cross sectional design. The population in this study is Women Age Fertile in Babatan Public Health Center area 2016. The sample used is 87 people with sampling technique using accidental sampling. Data collection techniques using questionnaires. Analysis of univariate data, bivariate using Chi Square test statistic and Independent sample T Test and multivariate using Logistic Regression. 87 WUS, 51.7% good knowledge, 55.2% negative attitude, 58.6% less information exposure, 51.7% higher education and average age of 33 years old. Bivariate analysis showed that there was a correlation between knowledge , attitude, exposure of information and education with early detection of cervical cancer at Babitis Public Health Center 2016. Factor for early detection of cervical cancer is exposure of information.It is suggested that health officers should work together with cadres to socialize and improve the extension to the community repeatedly in every activity, especially for people with low education, so that people want to do early detection of cervical cancer with IVA and papsmear.